Chemiluminescent Probes for Activity‐Based Sensing of Formaldehyde Released from Folate Degradation in Living Mice. Issue 25 (27th April 2018) - Bruemmer, Kevin J.; Green, Ori; Su, Timothy A.; Shabat, Doron; Chang, Christopher J.
Abstract: Formaldehyde (FA) is a common environmental toxin that is also produced naturally in the body through a wide range of metabolic and epigenetic processes, motivating the development of new technologies to monitor this reactive carbonyl species (RCS) in living systems. Herein, we report a pair of first‐generation chemiluminescent probes for selective formaldehyde detection. Caging phenoxy‐dioxetane scaffolds bearing different electron‐withdrawing groups with a general 2‐aza‐Cope reactive formaldehyde trigger provides chemiluminescent formaldehyde probes 540 and 700 (CFAP540 andCFAP700 ) for visible and near‐IR detection of FA in living cells and mice, respectively. In particular, CFAP700 is capable of visualizing FA release derived from endogenous folate metabolism, providing a starting point for the use of CFAPs and related chemical tools to probe FA physiology and pathology, as well as for the development of a broader palette of chemiluminescent activity‐based sensing (ABS) probes that can be employed from in vitro biochemical to cell to animal models. Abstract : Metabolic sensing : A first‐generation set of chemiluminescent activity‐based probes for in vivo imaging of formaldehyde (FA) is reported. A FA‐selective trigger is used to cage a phenoxy‐dioxetane scaffold that emits a photon after aza‐Cope‐dependent uncaging. These reagents were used to image FA fluxes in living cells and mice, enabling the unique identification of endogenous FA production from metabolic folate cycles in vivo.